Supporting Open Infrastructure through commercial partnerships: The Ubiquity case study - Hole, Brian (Septentrio Conference Series, 2022)
Watch the VIDEO. One of the key issues with open infrastructure within the scholarly communications and open science spaces is finding solutions for long-term sustainability. One important approach to this is ensuring that these infrastructures are also adopted and supported by the commercial sector, as in the case of key platforms we take for granted today, such as Linux. This can lead to significant benefits both for the scholarly community in terms of dependability and lower cost, and to companies in terms of lower risk, shared costs, and broadening impact on society. This presentation will present the approach taken by Ubiquity, a for-profit publishing services and open science platform, to base all of its products on open infrastructure. By deploying and contributing both financially and through open source code to infrastructure such as Open Journal Systems, Samvera repositories and OPERAS Metrics, Ubiquity is able to both strengthen these platforms for the wider community and to benefit significantly from their use. A cost-benefit analysis based on the Ubiquity example will be included to make the case for investment in open infrastructure by commercial companies. This will be further balanced by a discussion of ways to establish trust between the scholarly community and commercial providers, and the kind of guarantees these providers need to make based on our experience.